Risk factor for knee cartilage damage in patients with anterior cruciate ligament rupture - Xinwei Xiong; Dacheng Li; Yang Li; Qiangli Zhang (Medicine, 2026)
Anterior cruciate ligament (ACL) rupture is frequently accompanied by additional intra-articular lesions, among which articular cartilage-damage is clinically relevant because it may contribute to persistent symptoms and subsequent post-traumatic osteoarthritis. This retrospective observational study consecutively enrolled adults with primary unilateral ACL rupture treated between June 2020 and June 2025. Knee cartilage status was assessed using magnetic resonance imaging (MRI) and/or arthroscopic evaluation and graded according to the International Cartilage Repair Society classification; cartilage damage was defined as International Cartilage Repair Society grade ≥2. Demographic, injury-related, and imaging/surgical variables were extracted from the electronic medical record, radiology, and operative databases. Group comparisons were performed using t-tests or Mann–Whitney U tests for continuous variables and chi-square tests for categorical variables. Univariable and multivariable logistic regression models were applied to identify factors associated with cartilage damage. Among 80 patients, 32 (40.0%) had concomitant cartilage damage. Patients with cartilage damage had higher body mass index (BMI) and longer time from injury to surgery, and they more frequently exhibited medial and lateral meniscal tears. In multivariable analysis, higher BMI, longer injury-to-surgery interval, and both medial and lateral meniscal tears remained independently associated with cartilage damage, whereas age and bone marrow edema/bone contusion were not independently associated. These findings indicate that mechanical load-related factors and meniscal pathology are key correlates of cartilage damage in ACL rupture and may inform risk stratification at presentation. Given the modest sample size and wide confidence intervals for some estimates, these findings should be considered exploratory and hypothesis-generating pending confirmation in larger cohorts.